VD_FINDINFO AI 124/11 - 48/2012 vom 19. Dezember 2011 - VD Tribunal cantonal (2011)
SURVENANCE DU DOMMAGE, INCAPACITÉ DE TRAVAIL, RENTE EXTRAORDINAIRE | 28 al. 1 let. b LAI, 39 al. 1 LAI, 42 al. 1 LAVS